Effect of thermal cycling with various heating rates on the performance of thermoelectric modules - Riyadi, T.W.B. (Elsevier Masson s.r.l., 2022)
The thermoelectric module (TEM) offers a method to directly convert heat into electrical energy through the principle of the Seebeck effect. Unstable thermal cycling, however, can affect the performance of the TEM. In this work, the effects of thermal cycling at various heating rates on the electrical output of the thermoelectric system were investigated. An experimental rig was built to adapt the heating process and data measurements. Thermoelectric material was fixed between a heater plate on the hot side and a waterblock on the cold side of the TEM. An electrical power source was used to supply the heat energy in the heater plate to produce various heating rates for 100 cycles. The thermal cycling was controlled carefully. The temperatures of the hot and cold sides of the thermoelectric module were measured via thermocouples that were linked to a data logger for data acquisition. The results showed that an increase in the number of thermal cycles reduced the electrical output of the thermoelectric generator (TEG) system, which is composed of voltage, current, and power. The electrical output, however, increased at a lower heating rate. The increased internal resistance was responsible for the electrical drop. Â© 2022 Elsevier Masson SAS